The effect of casein and lactoferrin of bovine's milk on nestin expression of the exposed dental pulp - Ningtyas, Endah Ariyati Eko; Widjijono, Widjijono; Sunarintyas, Siti (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Pulp tissue can regenerate if damage occurs. The pulp differentiates into new odontoblast-like cells in Progenitor cells. Nestin is a marker of the presence of new dontoblast-like and expressed in pathological conditions. Bovine's milk casein and lactoferrin contain proteins that accelerate cell growth. This study aimed to determine the effect of casein and lactoferrin on the expression of nested cells in the exposed dental pulp.Method: The research method is an experimental laboratory with male 30 Spraque Dawley rats. Rats were grouped as : casein, lactoferrin, casein-lactoferrin, and Ca-(OH)2. Each group consisted of 15 samples of molars which were divided into 5 samples of teeth for observation on the 7, 14, and 21 days. The first molars of rats were prepared until the pulp was exposed. The data of nestin quantity with immunohistochemical (IHC) analysis on histological preparations were analyzed using two-way ANOVA then the least significance difference (LSD) test.Result: The results of the average number of nested cells on 7,14 and 21 days were highest on combination of casein and lactoferrin. Two-way ANOVA statistical proved that there was a significant difference (p<0.05) in each observation period and group and the number of expressions of nestin cells. LSD test showed that there was a significant difference (p<0.05) between groups compared to the control group.Conclusion: Combination casein and lactoferrin extracts affect the expression of the number of nestin cells as a marker of new odontoblast-like cells in the exposed dental pulp.